Modal Sosial Kelompok Langgak Craft Desa Koto Tandun Kecamatan Tandun Kabupaten Rokan Hulu - Masdelina Masdelina; Hesti Asriwandari; Nurhamlin Nurhamlin (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
The wealth of local potential existing in a community can inspire creativity which can create some opportunities for the community through establishing home-based businesses or what is now known as Home Industry. IKM Langgak Craft group is able to construct a palm oil stick waste processing plant considered as having contributing ability in the long term. The objective of current research is to analyze the elements of social capital contributing and the weaknesses of each social capital element in the IKM Langgak Craft group in Koto Tandun Village, Tandun  Sub District, Rokan Hulu Regency. This research used Putnam’s theory stating that social capital includes (1) trust, (2) norm/ethics, and (3) network. This research used qualitative methodology with purposive sampling technique; the author also lived in the location of research for 2 (two) months. The result of research analyzing the Bonding of IKM Langgak Craft group shows that the group has high solidarity. Strong solidarity social care), mutual help, and support for each other create emotional relation in the IKM Langgak Craft group as shown with sympathy and empathy appearing in the group. Bridging Social Capital can be seen from the net wok relation between IKM Langgak Craft group and other groups or IKMs; through this network, the IKM Langgak Craft group will exchange ideas and information on how to produce business innovation and other varying common knowledge.  The Linking Social Capital of IKM Langgak Craft group has fairly broad network that has been created since 2019-2022 with both governmental institutions and private companies around it.